A prospective observational study of outcomes from rehabilitation of elderly patients with moderate to severe cognitive impairment. (September 2016) - Vassallo, Michael; Poynter, Lynn; Kwan, Joseph; Sharma, Jagdish C; Allen, Stephen C
Objectives: To evaluate rehabilitation outcomes in patients with moderate to severe cognitive impairment. Design: Prospective observational cohort study. Setting: Rehabilitation unit for older people. Subjects: A total of 116 patients (70F) mean age (SD) 86.3 (6.4). Group 1: 89 patients with moderate cognitive impairment (Mini-Mental State Examination 11–20); and Group 2: 27 patients with severe cognitive impairment (Mini-Mental State Examination 0–10). Intervention: A personalised rehabilitation plan. Main measures: Barthel Activity of Daily Living score on admission and discharge, length of stay and discharge destination. Results: Of 116 patients, 64 (55.2%) showed an improvement in Barthel score. Mini-Mental State Examination was significantly higher in those who improved, 15.4 (SD 3.7) vs.13.2 (SD 5.1): p  = 0.01. The mean Barthel score improved in both groups; Group 1 – 14.7 (SD 19.1) vs. Group 2 – 9.3 (SD 16.3): p  = 0.17. Of 84 home admissions in Group 1, more patients returning home showed improvements of at least 5 points in the Barthel score compared with nursing/residential home discharges (32/37 – 86.5% vs. 10/28 – 35.7%: p  = 0.0001). In Group 2 of 17 home admissions, 6/6 (100%) home discharges showed improvement compared with 3/7 (42.8%) discharges to nursing/residential home ( p  = 0.07). In Group 1, a discharge home was associated with significantly greater improvement in number of Barthel items than a nursing/residential home discharge (3.27 (SD 2.07) vs. 1.86 (SD 2.32): p  = 0.007). A similar non-significant pattern was noted for severe cognitive impairment patients (3.5 (3.06) vs. 1.14 (1.06); p  = 0.1). Conclusion: Patients with moderate to severe cognitive impairment demonstrated significant improvements in Barthel score and Barthel items showing that such patients can and do improve with rehabilitation.